2017
DOI: 10.3390/toxins9070232
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Histone Methyltransferase DOT1 Regulates Aflatoxin and Pathogenicity Attributes in Aspergillus flavus

Abstract: Lysine methyltransferases transfer methyl groups in specific lysine sites, which regulates a variety of important biological processes in eukaryotes. In this study, we characterized a novel homolog of the yeast methyltransferase DOT1 in A. flavus, and observed the roles of dot1 in A. flavus. Deletion of dot1 showed a significant decrease in conidiation, but an increase in sclerotia formation. A change in viability to multiple stresses was also found in the Δdot1 mutant. Additionally, aflatoxin (AF) production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…One contributing factor to this defect in pathogenicity is that conidiation dramatically decreased in the ΔaflO and K241R site mutants when compared with WT, and development is thought to be one of the main factors in pathogenicity of A. flavus (Amaike and Keller, 2011). On the other hand, acetylation at K241 might change the structure of AflO, leading to inactivation of methyltransferase activity, which is similar to the defect of pathogenicity in methyltransferase knockout mutants of A. flavus (Liang et al, 2017). All this evidence revealed that acetylation is critical for pathogenicity in A. flavus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One contributing factor to this defect in pathogenicity is that conidiation dramatically decreased in the ΔaflO and K241R site mutants when compared with WT, and development is thought to be one of the main factors in pathogenicity of A. flavus (Amaike and Keller, 2011). On the other hand, acetylation at K241 might change the structure of AflO, leading to inactivation of methyltransferase activity, which is similar to the defect of pathogenicity in methyltransferase knockout mutants of A. flavus (Liang et al, 2017). All this evidence revealed that acetylation is critical for pathogenicity in A. flavus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that methyltransferases participated in various stress responses in A. flavus (Liang et al, 2017;Zhi et al, 2017). Therefore, the potential role of AflO (O-methyltransferase) with response to cell wall integrity, genotoxic and oxidative stresses was examined.…”
Section: Aflo Response To Cell Wall Integrity Stress In a Flavusmentioning
confidence: 99%
“…Dot1 is a H3K79 methyltransferase in yeast, and has not been studied in filamentous fungi heavily. A dot1 homolog (AFLA_093140) in A. flavus has been deleted, and shown to transcriptionally regulate the aflatoxin BGC (Liang et al, 2017). However, it remains unclear if this homolog does in fact regulate H3K79 methylation, or how prevalent this modification is in filamentous fungi.…”
Section: Writing the Codementioning
confidence: 99%
“…The cta1 deletion strain (ΔCTA1) and complementary strain (ΔCTA1:CTA1) were constructed according to previously described methods (Liang et al, 2017). Briefly, the upstream (AP) and downstream (BP) sequences of cta1 gene, as well as the pyrG gene of A. fumigatus were fused into the interruption fragment (AP-pyrG-BP) using fusion PCR strategy.…”
Section: Construction Of Mutantmentioning
confidence: 99%